Research Review on Defensive Strategies in Higher Education - Ismail Yusanto; Wijiharta SJ Dikara (PT FORMOSA CENDEKIA GLOBAL, 2024)
Competition in a less conducive macro environment has an impact on the decline of universities that are unable to compete. A study on the application of defensive strategies to 23 articles selected from 86 articles concluded that the threat of university decline was influenced by internal environmental factors (inaccuracy of the promotion mix), industrial environmental factors (changes in interest and competition) and macro environmental factors (college-age demographics, political policies, economic downturn, neoliberal education policies and pandemics). In a disadvantaged environment, universities are required to be observant, patient, and cautious in their awareness of crisis situations, so that they are able to take advantage of opportunities that are in line with the limitations of their strength to rise in new situations